Evolution of Dental Resin Adhesives—A Comprehensive Review - Waad Khalid Alomran; Mohammed Zahedul Islam Nizami; Hockin H. K. Xu; Jirun Sun (Journal of Functional Biomaterials)
This comprehensive review of dental resin adhesives explores their historical development, key components, recent innovations, and potential future directions, highlighting a dynamic and continually advancing field. From Buonocore’s breakthrough acid-etching technique and Bowen’s pioneering dental resin invention, successive generations of clinicians and scientists have pushed forward the technological and materials development for secure bonding, while preserving dental tissues. The review discusses the substantial advances in improving adhesive reliability, enabling more conservative treatment approaches. It also delves into enhancing fundamental adhesive components and their synergistic combinations. Recent innovations, including biostable and functional resins, nanotechnology, and bioactive components, address persistent challenges such as durability, antimicrobial efficacy, and therapeutic functionality. Emerging technologies, such as digital dentistry, artificial intelligence, and bioinspired adhesives, portend an exciting and promising future for dental adhesives. This review underscores the critical role of ongoing research in developing biocompatible, multifunctional, and durable adhesives. It aims to support dental professionals and researchers by providing a comprehensive understanding of the dynamic progression of dental adhesives, inspiring continued innovation and excellence in restorative dentistry.